The emergence of co-occurring adolescent polysubstance use and depressive symptoms: A latent growth modeling approach. (9th January 2015) - Felton, Julia W.; Kofler, Michael J.; Lopez, Cristina M.; Saunders, Benjamin E.; Kilpatrick, Dean G.
Abstract: This study tests competing models of the relation between depression and polysubstance use over the course of adolescence. Participants included a nationwide sample of adolescents ( N = 3, 604), ages 12 to 17 at study Wave 1, assessed annually for 3 years. Models were tested using cohort-sequential latent growth curve modeling to determine whether depressive symptoms at baseline predicted concurrent and age-related changes in drug use, whether drug use at baseline predicted concurrent and age-related changes in depressive symptoms, and whether initial levels of depression predicted changes in substance use significantly better than vice versa. The results suggest a transactional model such that early polysubstance use promotes early depressive symptoms, which in turn convey elevated risk for increasing polysubstance use over time, which in turn conveys additional risk for future depressive symptoms, even after accounting for gender, ethnicity, and household income. In contrast, early drug use did not portend risk for future depressive symptoms. These findings suggest a complicated pattern of interrelations over time and indicate that many current models of co-occurring polysubstance use and depressive symptoms may not fully account for these associations. Instead, the results suggest a developmental cascade, in which symptoms of one disorder promote symptoms of the other across intrapersonal domains.